2012
DOI: 10.4028/www.scientific.net/kem.503.67
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Micro Plastic Heat Radiator

Abstract: A new type of plastic micro heat radiators is designed in this paper. The radiator is prospected to be used in electronic system, chemical engineering system, etc. It is made of modified Phenylene sulfide with high thermal conductivity. A series of numerical simulations are carried out to optimize the structure of the radiator. The structure of the radiator includes the thickness of the fin and the distance between fins. The results show that the performance of the micro plastic heat radiator is very close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The heat dissipation of radiation is proportional to the radiation coefficient and the radiation area. The radiation coefficient of different materials is shown in Table 2 [5]. It is known that the heat dissipation performance of the radiator made by conductive plastics is better than that by the metal with the same structure.…”
Section: Led Heat Dissipation Mechanismmentioning
confidence: 99%
“…The heat dissipation of radiation is proportional to the radiation coefficient and the radiation area. The radiation coefficient of different materials is shown in Table 2 [5]. It is known that the heat dissipation performance of the radiator made by conductive plastics is better than that by the metal with the same structure.…”
Section: Led Heat Dissipation Mechanismmentioning
confidence: 99%
“…Surface structures have been considered as an effective way to enhance heat transfer properties under natural convection [7,14]. Lee et al [15] used a conventional mechanical machine to fabricate micro-channels with hydraulic diameters ranging from 318 to 903 μm on copper, and indicated that the heat transfer coefficient was inverse proportional to channel size at a given flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Test results are displayed in air pressure and coolant under the same pressure conditions, and the heat flow of polymer material microstructure heat exchanger can obtain cooling effect similar to the metal and ceramic. Bahadur and Bar-Cohen [12] and Han et al [13] studied the plastic radiator cooling effect. The results indicate that the plastic radiator can replace the metal radiator in certain situations.…”
Section: Introductionmentioning
confidence: 99%